Insights of School Head About Marketing Education Services Through Digital Media (Journal of Education and Educational Development, 2020)
This study mainly focuses on the insights of a private school’s head pertaining to the use of digital media in educational marketing. The qualitative research paradigm was chosen for this study and in depth phenomenological interview was conducted from a head of a private school. Two themes were extracted from the data: Marketing educational services through digital media and its challenges, and digital media tool for marketing education services. The study revealed that the school head perceived the digital media to be cost-effective marketing strategy that was multidimensional and value-driven, but due to lack of awareness, skills, attitude, and sense of maturity among stakeholders, digital media was ignored and was not much used as a cost-effective marketing tool. Nevertheless, it is proposed that by hiring marketing personnel to promote services professionally, by aligning their strategies according to the demands of their customers, and by inviting customers’ voice on digital platforms, digital media can become a cost-effective and a valuable tool for mercerization of education.